DAMPAK PERUBAHAN KEBIJAKAN PEMERINTAH TERHADAP PERMINTAAN DAN PENAWARAN PULP DAN KERTAS INDONESIA - Novindra Novindra; Anggriani Oktavia Sitanggang (Jurnal Bisnis Tani, 2016)
Pulp is one of the main materials in producing paper so that the supply for pulp will influence the paper production quantity. The quantities of pulp and paper productions to fullfill the domestic demand for pulp and paper are not enough. The study objective are: to analyze the factors that influence supply and demand for pulp and paper in Indonesia, and to evaluate the impact of interest rate subsidy for pulp and paper industry investment and the increase of paper's import tariff towards supply and demand for pulp and paper in Indonesia. This research was analysed by using econometric model in term of simultaneous equations that estimated by two-stage least squares method. The model specification of demand and supply for pulp and paper consisting of 16 equations (14 structural equations and 2 identity equations). The results showed that (1) the policy implementation of the interest rate subsidy for pulp and paper industries investment increases the pulp and paper production, and (2) the increase of paper's import tariff will protect the domestic paper industry from the foreign paper production.